Effects of liquid konjac on parameters related to obesity in diet-induced obese mice. Issue 7 (3rd July 2015) - Aoe, Seiichiro; Kudo, Haruka; Sakurai, Seiya
Abstract: Konjac-mannan has been suggested to exert a protective effect against visceral obesity. However, there is little knowledge about the effects of liquid konjac (LK) that is partially alkali gelled. The purpose of the present work was to evaluate the potential beneficial effects of a LK powder on obesity in mice. Male C57BL/6J mice were fed a high-fat diet supplemented with either 2.5 or 5% LK powder for 80 days. Growth parameters, abdominal fat content, serum biochemical markers, and hepatic lipid accumulations were measured. Dietary supplementation with LK resulted in decreased body weight gain and abdominal fat accumulation. Dose-dependent decreases were observed in accumulation of hepatic lipids and serum total cholesterol, leptin, insulin concentrations. The study findings indicated that LK had preventing effect against obesity, including the reduction of abdominal and hepatic lipid accumulation and serum parameters related to obesity. Graphical abstract: : Body weight (upper) and mesenteric fat (lower) in mice fed the test diets for 80 days. Error bars represent SD. Different superscript letters are significantly different ( p < 0.05).